2002
DOI: 10.1152/ajpregu.00251.2002
|View full text |Cite
|
Sign up to set email alerts
|

Membrane potential controls calcium entry into descending vasa recta pericytes

Abstract: We tested the hypothesis that constriction of descending vasa recta (DVR) is mediated by voltage-gated calcium entry. K(+) channel blockade with BaCl(2) (1 mM) or TEACl (30 mM) depolarized DVR smooth muscle/pericytes and constricted in vitro-perfused vessels. Pericyte depolarization by 100 mM extracellular KCl constricted DVR and increased pericyte intracellular Ca(2+) ([Ca(2+)](i)). The K(ATP) channel opener pinacidil (10(-7)-10(-4) M) hyperpolarized resting pericytes, repolarized pericytes previously depolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
61
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 34 publications
(60 reference statements)
8
61
0
Order By: Relevance
“…As expected for signaling via the ANG II AT 1 receptor, a classic peak-and-plateau intracellular Ca 2ϩ response is elicited in fura 2-loaded pericytes ( Fig. 3) (130,176). Both whole cell electrophysiological recording and measurements with a potentially sensitive fluorescent probe showed that ANG II depolarizes the pericyte cell membrane (Fig.…”
Section: Vasoactivity Of Dvrsupporting
confidence: 53%
See 4 more Smart Citations
“…As expected for signaling via the ANG II AT 1 receptor, a classic peak-and-plateau intracellular Ca 2ϩ response is elicited in fura 2-loaded pericytes ( Fig. 3) (130,176). Both whole cell electrophysiological recording and measurements with a potentially sensitive fluorescent probe showed that ANG II depolarizes the pericyte cell membrane (Fig.…”
Section: Vasoactivity Of Dvrsupporting
confidence: 53%
“…When exposed to ANG II, pericytes depolarize by activating a Cl Ϫ conductance, a process that gates voltage-activated Ca 2ϩ entry pathways (38,107,130,176). It is surprising is that this process apparently occurs in the juxtamedullary efferent circulation that supplies the renal medulla with blood flow but not in smooth muscle of superficial efferent arterioles (13-15, 63,64).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations